The Bradyrhizobium japonicum frcB Gene Encodes a Diheme Ferric Reductase - Small, Sandra K. (American Society for Microbiology, 2011)
Iron utilization by bacteria in aerobic environments involves uptake as a ferric chelate from the environment, followed by reduction to the ferrous form. Ferric iron reduction is poorly understood in most bacterial species. Here, we identified Bradyrhizobium japonicum frcB (bll3557) as a gene adjacent to, and coregulated with, the pyoR gene (blr3555) encoding the outer membrane receptor for transport of a ferric pyoverdine. FrcB is a membrane-bound, diheme protein, characteristic of eukaryotic ferric reductases. Heme was essential for FrcB stability, as were conserved histidine residues in the protein that likely coordinate the heme moieties. Expression of the frcB gene in Escherichia coli conferred ferric reductase activity on those cells. Furthermore, reduced heme in purified FrcB was oxidized by ferric iron in vitro. B. japonicum cells showed inducible ferric reductase activity in iron-limited cells that was diminished in an frcB mutant. Steady-state levels of frcB mRNA were strongly induced under iron-limiting conditions, but transcript levels were low and unresponsive to iron in an irr mutant lacking the global iron response transcriptional regulator Irr. Thus, Irr positively controls the frcB gene. FrcB belongs to a family of previously uncharacterized proteins found in many proteobacteria and some cyanobacteria. This suggests that membrane-bound, heme-containing ferric reductase proteins are not confined to eukaryotes but may be common in bacteria.